2022
DOI: 10.1111/liv.15249
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir disoproxil fumarate therapy to prevent hepatitis B virus vertical transmission—A review of maternal and infant outcomes

Abstract: Hepatitis B virus (HBV) is a global health problem. Vertical transmission of HBV from HBV surface antigen (HBsAg)-positive mothers to their infants is the most common cause of HBV infection worldwide. The use of passive-active immunoprophylaxis is >90% effective in reducing the risk of vertical transmission, but immunoprophylaxis failure can occur in infants born to mothers with high viraemia. Thus, it is recommended that pregnant women with HBV-DNA level >200 000 IU/ml receive nucleos(t) ide analogue (NA) tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 111 publications
0
9
0
Order By: Relevance
“…In addition to the mentioned HBeAg positive and <700S/CO, HBV DNA>5Log 10 IU/ml at delivery is a predictor of postpartum hepatitis. Postpartum hepatitis can occur in chronic HBV infected people receiving AVT or NAVT (120)(121)(122)(123). The increase rate of hepatitis during pregnancy and after delivery was 14% and 16%, respectively (5).…”
Section: High Risk Factors Of Postpartum Hepatitismentioning
confidence: 99%
“…In addition to the mentioned HBeAg positive and <700S/CO, HBV DNA>5Log 10 IU/ml at delivery is a predictor of postpartum hepatitis. Postpartum hepatitis can occur in chronic HBV infected people receiving AVT or NAVT (120)(121)(122)(123). The increase rate of hepatitis during pregnancy and after delivery was 14% and 16%, respectively (5).…”
Section: High Risk Factors Of Postpartum Hepatitismentioning
confidence: 99%
“…Multiples studies have shown that use of antivirals in the third trimester of pregnancy for those with a viral load above 200,000 IU/mL can markedly reduce the risk of vaccine failure, which may be as high as 10% in children born to highly viremic mothers even if appropriately vaccinated at birth (reviewed by [ 48 ]). A landmark study from China showed that tenofovir disoproxil fumarate (TDF) reduced the risk of perinatal transmission from those with viral loads above 200,000 IU/mL from 18% to 5% ( p = 0.007) [ 49 ].…”
Section: Case-finding Care and Antiviral Transmission Preventionmentioning
confidence: 99%
“…ULA formulations can also serve to improve patient compliance, as was observed for people living with HIV ( 17 ). Similarly, maternal-fetal transmission would be reduced by ULA formulations ( 18 ), along with transmission and reactivation for patients on immunosuppressive therapy ( 19 ).…”
Section: Introductionmentioning
confidence: 99%